EVALUATION OF IN-VIVO BIOLOGICAL ACTIVITIES OF STERCULIA DIVERSIFOLIA (G. DON) IN RELEVANCE TO THE ISOLATED SECONDARY METABOLITES - F. Rabbi1; A. Zada; A. Nisar; F.U. Khan; A. Rahim; M. Salman; A. Iqbal; A. Ullah; M. Sohail5. (Journal of Animal and Plant Sciences, 2020)
Genus Sterculia possess various types of compounds which have therapeutic potential. This study was aimed to explore the anticonvulsant, CNS depressant, analgesic, anti-inflammatory and anti-pyretic activities of Sterculia diversifolia stem bark and leaves extracts in mice. The secondary metabolites in MESD (methanolic extract of Sterculia diversifolia) was characterized by UV, IR, 1H-NMR, 13C NMR and 2D-NMR spectra in combination with EI-MS spectrometric techniques. Anticonvulsant and CNS depressant effect of MESD was assessed using strychnine-induced convulsion and phenobarbitone-induced hypnotic protocol. Analgesic activity was performed by acetic acid induced writhing and hot plate test while anti-inflammatory and anti-pyretic activities were assessed by carrageenan induced right hind paw edema and brewer’s yeast induced pyrexia. The isolation of compounds with different elucidation techniques (1H-NMR, 13C NMR and 2D-NMR spectra in combination with EI-MS spectrometric techniques) led to luteolin, isoquercitrin and ursolic acid. The current study results showed that crude MESD significantly (p < 0.05) delayed the onset, shortened the duration and offered protection against strychnine-induced convulsion. Crude MESD significantly (p < 0.05) prolonged the time of phenobarbitone-induced hypnosis. The analgesic response of crude MESD stem bark was more significant as compare to crude MESD leaves, while crude MESD also showed significant anti-inflammatory and antipyretic activity through dose dependent phenomenon. These significant results might be due to flavonoids (luteolin, isoquercitrin) and triterpenoids (ursolic acid) presence, though the involvement of other biologically active secondary metabolites cannot be overlooked.
Keywords: Sterculia diversifolia; Anticonvulsant; CNS Depressant; Analgesic; Anti-inflammatory; Anti-pyretic